Muscle Thickness of Anterior Mid-Thigh in Hospitalized Patients: Comparison of Supine and Standing Postures - Yasuda, Tomohiro (Arch Rehabil Res Clin Transl, 2020)
OBJECTIVES: To compare the magnitude changes in muscle thickness (MTH) of the anterior mid-thigh between the supine and standing postures. DESIGN: Experimental. SETTING: University hospital laboratory. PARTICIPANTS: Inpatients (N=283) between the ages of 29 and 93 years (193 men, 90 women) with cardiovascular disease who volunteered for this study. INTERVENTIONS: Not applicable. MAIN OUTCOME MEASURES: MTH of the anterior mid-thigh was measured with a 10 MHz ultrasound probe while the participants stood or lay supine in a relaxed position with their arms extended and by their sides. RESULTS: Age and percentage of body fat were greater (P<.01) in women than in men (74.3±12.3 vs 67.7±12.1y and 32.6±10.3% vs 27.4±7.4%, respectively), but standing height, body weight, and body mass index were greater (P<.01) in men than in women (164.9±6.3 vs 149.1±7.5 cm, 65.4±12.7 vs 49.5±11.1 kg, and 23.8±3.9 vs 22.1±4.4 kg/m(2), respectively). Correlations were found between the standing posture and supine position in the anterior-mid thigh MTH for both men (r=0.85; P<.01) and women (r=0.82; P<.01). In the anterior-mid thigh for men and women, MTH was greater in the standing posture (3.7±1.0 vs 2.5±0.7 cm) than in supine position (3.1±0.8 vs 2.1±0.7 cm) (both P<.01). CONCLUSIONS: In this study, MTH of the anterior mid-thigh during prolonged hospitalization was approximately 16% higher in men than in women regardless of posture, and was approximately 32% higher in standing posture than in the supine position regardless of sex.